High-Grade Transformation in Adenoid Cystic Carcinoma of the Bartholin Gland: Case Report - Santiago, Aline Evangelista [UNESP]; Teunissen, Nicky; Ricardo, Bernardo Ferreira De Paula; Cândido, Eduardo Batista; Furtado, Rafaela De Souza; Silva Filho, Agnaldo Lopes Da [UNESP] (Federação das Associações de Ginecologia e Obstetrícia, 2021)
Introduction In the present study, we report a case of primary adenoid cystic carcinoma (ACC) of the Bartholin gland with high-grade transformation (HGT). Adenoid cystic carcinoma of the Bartholin gland is a rare tumor and HGT has only been reported in head and neck tumors. Case Report A 77-year-old woman with a non-ulcerated vulvar lesion on the topography of the right Bartholin gland. The patient was submitted to tumor resection followed by V-Y island flap and adjuvant radiotherapy. The histopathological examination revealed primary ACC of the Bartholin gland, with areas of HGT and extensive perineural invasion. The immunohistochemical study with p53 showed a diffuse and strong positive reaction in areas with HGT. After 24 months of follow-up, the patient presented distant metastases and died, despite having undergone to chemotherapy. Conclusion As far as we know, this case is the first description in the literature of HGT in ACC of the Bartholin gland, and HGT appears to be associated with tumor aggressiveness.
Keywords: adenoid cystic carcinoma; Bartholin gland; gynecology; oncology; vulvar neoplasms